Galerie Wanda Reiff Maastricht : Tentoonstellingen 1989. - Galerie Wanda Reiff, Maastricht (Maastricht : Galerie Wanda Reiff, 1989)
Garcia Sevilla, Ferran ; Claessen, Wim ; Penone, Giuseppe ; Slits, Ton ; Saiz, Manuel ; Copers, Leo ; Vugs, Joop ; van Sprang, Annemarie ; Kirkeby, Per ; Mostard, Yvonne ; Parmiggiani, Claudio
Nederlands & Engels
boek